Exploring quality of life of children with cerebral palsy and intellectual disability: What are the important domains of life? - Elise Davis; Dinah Reddihough; Nada Murphy; Amy Epstein; Susan Reid; Andrew J. O. Whitehouse; Katrina Williams; Helen Leonard; Jenny Downs (2017)
Although it is estimated that half of all children with cerebral palsy also have comorbid intellectual disability, the domains of quality of life (QOL) important for these children are not well understood. The aim of this study was to identify important domains of QOL for these children and adolescents.Due to the children's communication impairments, qualitative semi-structured interviews were conducted with 18 parents. The children (9 males) had a median age of 12 (range 7 to 17) years at interview and nearly two thirds were classified as Gross Motor Function Classification System IV or V. A grounded theory approach was used to identify domains of QOL.The 11 domains identified as important to QOL were physical health, body comfort, behaviour and emotion, communication, predictability and routine, movement and physical activity, nature and outdoors, variety of activity, independence and autonomy, social connectedness, and access to services.The domains of QOL that emerged from this study will be useful for professionals who support children with cerebral palsy and their families. They will also be important for developing a QOL instrument essential for informing the development of interventions and their monitoring and evaluation.